THE FISHERY AND BIOLOGY OF CRABS OF KAKINADA REGION - Devi, S Lalitha (Indian Journal of Fisheries, 2011)
Kakinada area has a lucrative crab fishery throughout the year with peaklandings during March to May and August to November. The morphometricrelationships, age and growth, size at maturity, breeding season and sex ratioin PorUtmis pelagicus, P. sangiiinolentiis and Scylla serrata are reported. Therelation of fecundity to carapace length in P. sanguinolentiis is discussed. Anincidence of infection in Charybdis cnwicUa by a rhizocephalan was noticed.Jn P. sanguinolentiis 21% of the eggs were infested by parasitic copepods